Investigation of proton exchange membrane fuel cell stack with inversely phased wavy flow field design. (1st January 2022) - Yin, Cong; Song, Yating; Liu, Meiru; Gao, Yan; Li, Kai; Qiao, Zemin; Tang, Hao
Highlights: A metallic bipolar plate fuel cell stack with 315 cm 2 active area is designed. A 3D two-phase model is developed for performance uniformity analysis. Inversely phased wavy flow fields for anode/cathode are investigated. Thermal convection of coolant is enhanced with periodic secondary flow. Membrane temperature distributes with multiple island shaped 2D patterns. Abstract: The proton exchange membrane fuel cell stack based on metallic bipolar plate is promising in fuel cell vehicle applications due to its compact design and high power density. As the flow field design is critical to the fuel cell performance, in this work, the novel wavy flow fields designed in metallic bipolar plate with inverse phase for anode and cathode are investigated by both experiment and simulation. Validated by the test of 5-cell short stack with 315 cm 2 active area, a three-dimensional non-isothermal model is developed to investigate the multi-physical processes and internal parameter uniformities of the presented stack design. The in-plane parameter distributions of current density, water content and reactant concentrations basically follow the cathode wavy flow field geometry rather than the anode one, while the temperature distribution presents multiple elliptical island shaped patterns according to the intercrossed wavy flow fields. The two-layered intercrossed wavy coolant channels enhance the thermal convection of the coolant which induces interlaminar secondary flow with 25% velocity magnitude of the primary one. The findings of this work are beneficial to understand the internal behavior of the fuel cell stack and optimize the flow field design for enhanced performance and heat dissipation capability.